Impact of safety leading indicators on workplace safety conditions at a selected mine and the influence of this on workplace safety - Masemula, Floyd (University of the Witwatersrand, Johannesburg, 2021)
Safety leading indicators are precursors and can give warning on potential failures or harm. As such, they enable organisations to proactively identify safety problems, and facilitate implementation of measures to prevent occurrence of accidents or incidents. Recent developments in occupational health and safety management emphasises the use of safety leading indicators, and the SA mining industry has adopted to these developments. This study aims to determine the impact of safety leading indicators on workplace safety conditions in the context of an underground mine, and determine the influence of leading indicators on workplace safety outcomes. Two hypothesis are developed to achieve these objectives,: (1) there is a statistically significant relationship between the safety leading indicators and safety conditions, (2) there is a statistically significant relationship between safety leading indicators and workplace safety outcomes. To test these hypotheses, the Organisational Performance Metric-Monash University (OPM-MU) survey tool was used to measure leading indicators, while data for workplace safety conditions and safety outcomes was collected from the reports at the selected mine. Data was analysed using one-way ANOVA to test for statistical significance between the chosen variables. The results showed that there is no statistically significant relationship between safety leading indicators and workplace safety conditions, and that there is a statistically significant relationship between safety leading indicators and safety outcomes. The findings concerning Hypothesis 1 reveal that risk ratings of workplace safety conditions may not be the best representation of the variable of workplace safety conditions, and that other factors highlighted in the chosen interpretive framework for this study affect safety conditions. While the results of this study found there is a statistically significant relationship between safety leading indicators and safety outcomes, it is however a weak one. The implications of this is that safety leading indicators are more concerned with the circumstances preceding and giving rise to the safety outcomes rather than the safety outcomes themselves
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand
Keywords: Safety leading indicators; Safety conditions; Safety outcomes; UCTD; SDG-8: Decent work and economic growth